Construction trucks - Dussling, Jennifer; Courtney (New York : Grosset & Dunlap, 1998)
Describes the jobs which various kinds of trucks and other construction equipment do on a work site.
Keywords: Trucks -- Juvenile literature; Construction equipment -- Juvenile literature; Trucks; Construction equipment